2014
DOI: 10.1063/1.4869125
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous large electrical capacitance of planar microstructures with vanadium dioxide films near the insulator-metal phase transition

Abstract: The temperature dependence of electrical capacitance of planar microstructures with vanadium dioxide (VO2) film near the insulator-metal phase transition has been investigated at the frequency of 1 MHz. Electrical capacitance measurements of the microstructures were performed by the technique based on the using of a two-terminal resistor-capacitor module simulating the VO2 layer behavior at the insulator-metal phase transition. At temperatures 325–342 K, the anomalous increase in microstructures capacitance wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…VO 2 exhibits metal–insulator transitions (MITs) and structural phase transitions near room temperature 1 . The coexistence of metallic and insulating domains in VO 2 thin films and its influence on the physical properties have been investigated extensively 3 6 7 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 . Analyses of the macroscopic physical properties of VO 2 often require careful consideration of the geometric configuration of the domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…VO 2 exhibits metal–insulator transitions (MITs) and structural phase transitions near room temperature 1 . The coexistence of metallic and insulating domains in VO 2 thin films and its influence on the physical properties have been investigated extensively 3 6 7 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 . Analyses of the macroscopic physical properties of VO 2 often require careful consideration of the geometric configuration of the domains.…”
mentioning
confidence: 99%
“…Analyses of the macroscopic physical properties of VO 2 often require careful consideration of the geometric configuration of the domains. Recently, Ramíez et al and Aliev et al reported anomalous behavior in AC impedance spectra of VO 2 thin films 22 23 . These experimental data suggest that ultra-thin, highly conductive domains exist below the transition temperature, and that the domain boundaries have a fractal nature near the transition temperature.…”
mentioning
confidence: 99%
“…Although the role of capacitor in our circuit plays the external capacitor, C 0 , the internal VO 2 capacitance may also play the same role, 30,31 since the oscillations are observed in voltage-controlled mode without any external capacitor. 18,19 The short duration of high-temperature conductive channel existence in the VO 2 film at oscillations is indirectly indicated by the fact that the temperature distribution at the oscillations [ Fig.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13] The percolative character of the MIT in VO 2 films has been emphasized several times. 9,[14][15][16][17] It should be noted that the properties of VO 2 -based materials around the MIT are not only of theoretical interest but also influence, for example, the energy-savings potential of thermochromic glazings. 18 Percolation enhances macroscopic resistance fluctuations, as is well known, 19 and such fluctuations have been investigated in some prior studies 20-23 especially with regard to bolometer performance.…”
Section: Introductionmentioning
confidence: 99%